Vibration Characteristics of Beam Structure Attached with Vibration Absorbers at its Vibrational Node and Antinode by Finite Element Analysis - W. S. Ong; Muhd Hafeez Zainulabidin (LPPI Universitas Muhammadiyah Kalimantan Timur (UMKT), 2020)
In this study, the vibration characteristics of fixed ends beam are analysed after attached with dynamic vibration absorbers at vibrational node and antinode by simulation using ANSYS APDL. This study aim to obtain the best location and optimum number of DVAs placed on the fixed ends beam in order to reduce vibration of beam. The dynamic vibration absorber were attached to the fixed ends beam vibrational node and antinode for a total of three modes of vibration. The 0.84 m long beam is modelled by ANSYS and divided into 21 elements where each element is 0.04 m. A harmonic force, Fo of 28.84 N is exerted at node 3 of beam element. Modal analysis and harmonic analysis are carried out in this study to obtain the natural frequency and frequency response of the beam respectively. The vibration characteristics of fixed ends beam without DVA and beam attached with DVAs were compared. The simulation results show reduction of vibration amplitude of the beam especially when the DVA were attached at the vibrational antinode. The DVA amplitude increase when amplitude of beam decreases. From this study, it is proved that DVAs absorb vibration of the beam structure. The best position to attach DVAs is the vibrational antinode based on the modes of vibration. The increment of DVAs number will not affect the percentage reduction of vibration amplitude as long as the DVAs are placed at optimum location.